ANALISIS POLA INTERAKSI FANWAR K-POP DI MEDIA SOSIAL X DI ANTARA FANDOM STAY: : STUDI ETNOGRAFI VIRTUAL - Siti Ilmi Nurfa'idhah Yatni (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2025)
This study analyzes the fanwar phenomenon within the K-Pop fan community, specifically the Stray Kids (Stay) fandom on social media X. The problem raised is how internal conflicts within the fandom arise due to biased favoritism, offensive inside jokes, and violations of fan ethics that stem from the phenomenon of K-Pop fan fanaticism. The purpose of this study is to identify the active and reactive interaction patterns of the Stay fandom in responding to fanwars and to understand their community culture when fanwars occur within the internal fandom community. This study uses a qualitative method with a virtual ethnography approach, through participant observation, content documentation, and cyber media analysis. The theoretical basis of the study refers to Symbolic Convergence Theory and Computer Mediated Communication (CMC). The results show that the active interaction of the Stay fandom when responding to fanwars includes the use of hashtags and do cleaning timeline, while reactive interactions include call outs, mass reports and blocks, and calls for peace between fans. The contribution of this study lies in the development of virtual ethnographic studies in the context of online fandom communication and broadens understanding of the dynamics of conflict and solidarity in digital popular culture.